2013
DOI: 10.3168/jds.2013-6651
|View full text |Cite
|
Sign up to set email alerts
|

Particle size alterations of feedstuffs during in situ neutral detergent fiber incubation

Abstract: Particle size alterations during neutral detergent fiber (NDF) determination and in situ rumen incubation were analyzed by dry sieving and image analysis to evaluate the in situ procedure for estimation of NDF degradation parameters and indigestible NDF concentration in terms of particle size. Early-cut and late-cut grass silages, corn silage, alfalfa silage, rapeseed meal, and dried distillers grains were examined. Treatments were (1) drying and grinding of forage samples and grinding of concentrates; (2) neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Digesta particle size was not measured in this study but effects of particle size on K 1 have been reported in the literature. For grass silage in particular, advancing plant maturity was observed to increase K 1 in line with a reduced digesta particle size and increased particle breakdown rate for the small particle pool in the rumen for a late-cut compared with an early-cut grass silage (Rinne et al, 2002;Krämer et al, 2013). Similarly, advancing maturity stage of grass silage considerably decreased the proportion of large particles (>1.0 mm) and increased that of small particles (0.2-0.5 mm) in feces (Jalali et al, 2012).…”
Section: Effect Of Maturity Stage and Fertilizationmentioning
confidence: 93%
“…Digesta particle size was not measured in this study but effects of particle size on K 1 have been reported in the literature. For grass silage in particular, advancing plant maturity was observed to increase K 1 in line with a reduced digesta particle size and increased particle breakdown rate for the small particle pool in the rumen for a late-cut compared with an early-cut grass silage (Rinne et al, 2002;Krämer et al, 2013). Similarly, advancing maturity stage of grass silage considerably decreased the proportion of large particles (>1.0 mm) and increased that of small particles (0.2-0.5 mm) in feces (Jalali et al, 2012).…”
Section: Effect Of Maturity Stage and Fertilizationmentioning
confidence: 93%
“…However, according to the results of this study, this recommendation seems not to be valid when F57 is used. By considering the maximal estimate of critical time for NDF (274.5 h) and adopting a multiple of 24 h to build an analytical recommendation, at least 288 h (12 d) are necessary to obtain a reliable estimate of the undegradable fraction of NDF, according to the results of and Kra¨mer et al (2013). Second, the greater critical times obtained with F57 and NWT compared with nylon were directly caused by lower degradation rates (Fig.…”
Section: Ruminal Degradation Profilesmentioning
confidence: 99%
“…Different particle sizes are used in such procedures (Bowman and Firkins 1993;Nocek and Kohn 1988;Kra¨mer et al 2013). Nocek (1988) suggested using screen sieves of 2 mm and 5 mm for concentrate and forage to compensate the lack of rumination of samples.…”
Section: Particles Sizesmentioning
confidence: 99%
“…Furthermore, lignin can be modified through the passage in the digestive tract (Fahey and Jung, 1983), and this can cause differences in recovery rate. Indigestible NDF can be lost from the dacron bags as particles during determination of INDF, and the particle loss might differ between feeds, and this might also lead to differences in recovery rate (Krämer et al, 2013). Simultaneous use of two internal markers could be an advantage in studies with part time grazing, but marker ratio must deviate substantially between herbage and barn feed, and furthermore recovery of markers should be known.…”
Section: Indigestible Fibre Ratiomentioning
confidence: 99%